The Awakening of the Dormant Mount Vettore Fault (2016 Central Italy Earthquake, Mw 6.6): Paleoseismic Clues on Its Millennial Silences. Issue 2 (22nd February 2019) - Galli, P.; Galderisi, A.; Peronace, E.; Giaccio, B.; Hajdas, I.; Messina, P.; Pileggi, D.; Polpetta, F.
Abstract: The Mount Vettore normal fault ruptured between August and October 2016, sourcing three earthquakes of M w 6.2, 6.1, and 6.6. The first one caused the death of 299 people, while the entire sequence reached the highest macroseismic intensity levels in Italy since the catastrophic 1915 Fucino event ( M w 7.1). This fault was known to be one of the historically dormant faults of the Italian Apennines, and its sudden activation, not preceded by any foreshocks, has caught people and scientists off guards. We describe here the results from three new paleoseismic trenches opened across splays of the main antithetic fault that ruptured at surface on 30 October together with the 30‐km‐long Mount Vettore master fault. Data account for six surface faulting events since 9 ka, with a return time of 1.8 ± 0.3 kyr. The penultimate, probably stronger earthquake occurred in Late Roman times, perhaps in 443 AD, when also Rome suffered damage to its monumental buildings. Once again, paleoseismology turns out to be a powerful tool in seismic hazard assessment, especially for earthquakes that recur hundreds or thousands of years apart. Plain Language Summary: Twenty years before the frightful central Italy earthquake of 2016 ( M w 6.6), early paleoseismic trenches revealed the existence and Holocene activity of the Mount Vettore fault system, in the Italian Apennines. New trenches excavated across the 2016 surface ruptures have allowed to define five paleoearthquakes of similar magnitude, the last one occurred in Late Roman period, when also the far monumental building of Rome were damaged. By joining the results of the new paleoseismic analyses with those published 20 years ago, the authors have found that the return time for such a class of magnitude earthquakes is about 1, 800 years. Key Points: Three new paleoseismic trenches have been excavated across the Mount Vettore fault system Recurrence time for the past five, 2016‐like earthquakes ( M w 6.6) is about 1, 800 years The largest earthquakes sourced by the Mount Vettore fault damaged the most famous monuments in Rome